2020
DOI: 10.22541/au.159225410.03302606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root vacuolar sequestration and suberization contribute to salinity tolerance in Pistacia spp. rootstocks

Abstract: Pistachio (Pistacia spp.) is a tree nut crop with relatively high salinity tolerance. Currently, limited information exists on its rootstock's cellular responses to salinity stress, especially in its roots. In this study, we investigated salinity tolerance at cellular level, in two pistachio rootstocks, Pistacia integerrima (PGI) and a hybrid, P. atlantica x P. integerrima (UCB1). Root tip sections were categorized across a developmental gradient according to their xylem development, and their sodium content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(135 reference statements)
1
0
0
Order By: Relevance
“…This indicates nucleolar stress (Yang et al, 2018) triggered by both neuSAL and alkSAL that leads to the activation of the protein synthetic machinery in the studied demes (Figure S6B). Moreover, enhanced activation of 2 genes involved in suberin deposition (FAR1, FAR5)previously reported to be transcriptionally induced by salinity (Domergue et al, 2010) -were observed in all demes under neuSAL and alkSAL (Figure S6C), which suggests that increase of suberin deposition may enhance tolerance to neutral and alkaline salinity (Zhang et al, 2021).…”
Section: Kegg Erichment Analysis Of Coresal Degssupporting
confidence: 52%
“…This indicates nucleolar stress (Yang et al, 2018) triggered by both neuSAL and alkSAL that leads to the activation of the protein synthetic machinery in the studied demes (Figure S6B). Moreover, enhanced activation of 2 genes involved in suberin deposition (FAR1, FAR5)previously reported to be transcriptionally induced by salinity (Domergue et al, 2010) -were observed in all demes under neuSAL and alkSAL (Figure S6C), which suggests that increase of suberin deposition may enhance tolerance to neutral and alkaline salinity (Zhang et al, 2021).…”
Section: Kegg Erichment Analysis Of Coresal Degssupporting
confidence: 52%